2012
DOI: 10.1111/pan.12076
|View full text |Cite
|
Sign up to set email alerts
|

The paracetamol concentration‐effect relation in neonates

Abstract: SummaryObjectives: We suggested a loading dose (20 mgÁkg À1 ) followed by 10 mgÁkg À1 q6h of intravenous (IV) paracetamol to achieve an effect compartment concentration of 11 mgÁl À1 in neonates. Since there are no pharmacodynamic data to support such an effect compartment concentration, pain scores collected in neonates treated with an IV paracetamol loading dose (20 mgÁkg À1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 23 publications
(57 reference statements)
3
61
3
Order By: Relevance
“…The fact that it has recently been described that the effect compartment concentration of 10 mg/L of acetaminophen, achieved following a loading dose administration (20 mg/kg, intravenous) in neonates, is effective for moderate pain relief further provides evidence that the absence of effects likely at least in part relates to insufficient dosing [180].…”
Section: Acetaminophen (Paracetamol)mentioning
confidence: 96%
See 1 more Smart Citation
“…The fact that it has recently been described that the effect compartment concentration of 10 mg/L of acetaminophen, achieved following a loading dose administration (20 mg/kg, intravenous) in neonates, is effective for moderate pain relief further provides evidence that the absence of effects likely at least in part relates to insufficient dosing [180].…”
Section: Acetaminophen (Paracetamol)mentioning
confidence: 96%
“…• Data on acetaminophen pharmacokinetics/dynamics have been published and suggest that the same effect compartment concentration (10 mg/L) of acetaminophen should be aimed for in neonates [174,175,180].…”
Section: Take-home Messagesmentioning
confidence: 98%
“…While there are data from pharmacokinetics studies [12,13], the pharmacodynamics of paracetamol in neonates are poorly described. Allegaert et al [14] showed a reduction of pain after 20 mg/kg of paracetamol in preterm and term infants suffering from delivery trauma. Pharmacokinetics studies on intravenous paracetamol in preterm infants also suggest that a loading dose of 20 mg/kg intravenous paracetamol for neonates with postconceptional ages of 28-32 weeks and body weights above 1.5 kg is sufficient for pain relief [15].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, paracetamol is an analgesic drug with proven efficacy also in very young patients [53,54 && ], a causal relation between its use and the development of asthma is not proven [55 && ]. NSAIDs and dexamethasone are administered for the prevention of post-tonsillectomy pain.…”
Section: Painmentioning
confidence: 99%